2016
DOI: 10.1111/1471-0528.13862
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention to limit gestational weight gain: the Norwegian Fit for Delivery randomised controlled trial

Abstract: Objective To examine whether a lifestyle intervention in pregnancy limits gestational weight gain (GWG) and provides measurable health benefits for mother and newborn.Design Randomised controlled trial.Setting Healthcare clinics of southern Norway.Population Healthy, non-diabetic, nulliparous women, aged ≥18 years, with a body mass index of ≥19 kg/m 2 , and with a singleton pregnancy at ≤20 weeks of gestation.Methods Women were randomised to an intervention group (with dietary counselling twice by telephone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
169
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(176 citation statements)
references
References 43 publications
4
169
0
3
Order By: Relevance
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
“…Twenty two studies17343637383941424748515253565758596061626367 were from Europe, four each from North America,44546566 Australia,16434550 and Brazil,35495564 and one study each from Egypt40 and Iran 46. Twenty three IPD studies included women of any body mass index (BMI),3435363738424445464748525455565859606164656667 seven included only obese women,17394041506263 and six included obese and overweight women 164349515357. The interventions included those mainly based on diet (four IPD studies)47616264 or physical activity (16 IPD studies),3536374246495051525558596566…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Phelan et al reported no effect of prenatal exercise + co-intervention (diet and behavioural intervention) on the odds of returning to pre-pregnancy weight at 12 months postpartum (OR 1.6, 95% CI 0.92 to 2.7) 72. In contrast, Sagedal et al 63 reported higher odds of returning to pre-pregnancy weight at 12 months postpartum (OR 1.50, 95% CI 1.01 to 2.24) in women who participated in an exercise + diet intervention. Similarly, Rauh et al reported lower odds of PPWR >5 kg at 4 months postpartum (OR 0.5, 95% CI 0.2 to 0.9, adjusted for several potential confounding factors)55 and at 12 months postpartum (OR 0.40, 95% CI 0.16 to 0.97, adjusted for age, pre-pregnancy BMI, time of 12-month follow-up and practice)77 with a prenatal exercise + diet intervention compared with no intervention.…”
Section: Resultsmentioning
confidence: 97%
“…Of 1610 nulliparous women, 606 were included into the study [26], and 575 participated in the present sub study (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%